(3GdeQGSes - (3GdOjdej GdWHQSJGfj, HSGdGQ Ch HSqdGQ, MeRI Hf YHO GdYRjR, J (B463 (3g`s
(3ChdgG (B:s
(3GdMeO ddg (B...(3hbO YReJ Ydi LeY cJGH eNJUQ jLeY cd QSe hjMhj cd MJe ef GdTQjYI(B. (3hCJjJg Ydi GdbSeI djbQH MaXg (B...(3Cbhd ChdG(B: (3Ef GdQShe GdTQYjI JfbSe bSejf(B: (3YHGOGJ heYGedGJ(B...s
(3BNQgG (B:s
(3abO CJjfG aj gPG GdcJGH Ydi cJH Gdabg eY GdGNJUGQ(B...(3hde fUfag dbUhQ GdcJH GdeUfaGJ YeG ajg, Hd dCf CUMGHfG QVhGf Gddg Ydjge EPG GNJUQhG, CKHJhG GdYHGOGJ, hde jPcQhG GdeYGedGJ(B. (3hdCfg Ydi WQjbI ef GdbSeI ZjQ eCdhaI, hedjI ZjQ eYQhaI(B.s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B2\278s
(3gOjI GdYGQajf (B1\380s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis